Application of the Mirrorball High-Sensitivity Cytometer to Multiplexed Assays for Antibody Drug Discovery. (April 2015) - England, Elizabeth; Newton, Philip; Neal, Frances; Kitching, Lisa; Colley, Caroline; Rossant, Christine J.
Highly sensitive, high-throughput assay technologies are required for the identification of antibody therapeutics. Multiplexed assay systems are particularly advantageous because they allow evaluation of several parameters within 1 well, increasing throughput and reducing hands-on laboratory time. The mirrorball (TTP Labtech), using high-throughput fluorometric microvolume assay technology, offers simultaneous scanning with up to 3 lasers as well as laser scatter detection. This makes the mirrorball especially suitable for the development of highly sensitive and multiplexed assays. We have developed bead- and cell-based binding assays that demonstrate how the multilaser capability of the mirrorball can be exploited to enhance assay sensitivity. In addition, using the multilaser simultaneous scanning capability, we have established multiplexed cytokine quantitation assays and antibody–cell binding assays. Our results demonstrate the potential utility of this technology to improve the sensitivity and efficiency of biologics screening, resulting in streamlining of the lead antibody selection process.